KRITERIA PERSAMAAN PADA POKOKNYA DALAM SENGKETA MEREK TIMBERLAND DENGAN MEREK TIMBERLAKE: Substantial Similarity Criteria in The Timberland With Timberlake Trademark Dispute - Amelia, Putri Sherina; Lestari, Suci (AMICUS CURIAE, 2024)
- The dispute on the Timberland brand with the Timberlake brand happened caused by substantial similarity which was being sued on similarities in pronunciation, type of goods, and visuals which decided in Commercial Court Decision Number 42/Pdt.Sus-Merek/2020/PN.Niaga.Jkt.Pst and Number 881 K/Pdt.Sus-HKI/2021. The problem in this journal is how to determine the substantial similarity criteria in the dispute on the Timberland and Timberlake brands based on Article 21 (1) of Law Number 20 of 2016 on Trademarks and Geographical Indications? and whether the implementation of substantial similarity criteria on Commercial Court Decision Number 42/Pdt.Sus-Merek/2020/PN.Niaga.Jkt.Pst jo. Number 881 K/Pdt. Sus-HKI/2021 is  fulfill Article 21 (1) of Law Number 20 of 2016 on Trademarks and Geographical Indications? The results of the study, the determination of the substantial similarity criteria of the dispute on the Timberland and Timberlake brands is accordance  Article 21 (1) of Law Number 20 of 2016 on Trademarks and Geographical Indications and the implementation of the substantial similarity criteria on Decision Number 42/Pdt.Sus-Merek/2020/PN.Niaga. Jkt.Pst is not fulfill the criteria on Article 21 (1) of Law Number 20 of 2016 on Trademarks and Geographical Indications and the implementation of the substantial similarity criteria in Decision Number 881 K/Pdt.Sus-HKI/2021 is fulfill the criteria on  Article 21 (1) of the Law Number 20 of 2016 on Trademarks and Geographical Indications